PENGARUH DIMENSI - DIMENSI EMPOWERMENT TERHADAP KINERJA KARYAWAN PADA PT DJINAWI GRESIK - Heri Kusairi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
The development of business circumtances that always changes, leads companies to have competitive advantages in efficiency and effectivity. PT. Djinawi is a self-focused contractor company in optimalizing its human resources assets by adapting the empowerment to be successful in market competition. Such adapting of empowerment is viewed from four psychological empowerment dimensions that had been introduced by Spreitzer. Those foour dimensions are meaning, competence, self-determination, and impact. If all of these four dimensions, e.g., meaning, competence, self-determination, and impact is felt by employees, then the empowerment process will go through in good condition. This research used a holistic single case study, by using the technique of data collection by interview, direct-observation, and internal data of company. For the needs of mapping, a pra-case study had been carried out. From this research, it revealed that the adapting of empowerment can go through well, which viewed from the four dimensions, e.g, meaning, competence, self-determination, and impact that has been felt by employees. In line with it, from the triangulation may be obtained that the respondents also expressed some obstacles in project staff level. It can be concluded that if all of four dimensios, e.g, meaning, competence, self-determination, and impact could be felt by employees, then empowerment can go through well as well as make a company success in face against a tight of market competition.